ByzRev 03.2021.001: Dimiter Angelov, The Byzantine Hellene: The Life of Emperor Theodore Laskaris and Byzantium in the Thirteenth Century.: Cambridge: Cambridge University Press 2019. - Katsoni, Polymnia (The Byzantine Review, 2021)
Dimiter Angelov, The Byzantine Hellene: The Life of Emperor Theodore Laskaris and Byzantium in the Thirteenth Century. Cambridge: Cambridge University Press 2019. 460 pp. – ISBN: 978-1-108-48071-0 (€40,30)